PENGARUH KUALITAS KEPEMIMPINAN, DISIPLIN KERJA, DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA PT. INDRI PLANT PKS NAPAL KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU RIAU - Ira Susanti; Zulfadil Zulfadil (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyze the influence of leadership quality, work discipline, and teamwork on employee performance at Pt. Indri Plant PKS Napal. Employee performance is one of the important factors in supporting the achievement of company goals. The sample of this study was all 88 employees using census techniques. This study uses a quantitative descriptive approach and the data analysis technique used is multiple linear regression analysis, where variables are measured using a Likert scale, data collection methods using questionnaires. Data processing uses SPSS software. The results of this study indicate that the variables of leadership quality, work discipline, and teamwork have an effect on employee performance both partially and simultaneously. The R Square value of 0.489 or 48.9% indicates that the variables of leadership quality, work discipline, and teamwork as a whole have an effect of 48.9% on employee performance, while the remaining 51.1% is influenced by other variables not examined in this study